Non-linear dependencies in African stock markets: Was subprime crisis an important factor? - Ferreira, Paulo (2019)
The historical dependence in stock markets it is a very explored issue, especially in developed markets. In this paper we try to address the question of global dependency in African stock markets, and for that purpose we use a global approach able to capture the long-term dependencies being linear or non-linear ones. Are there significant differences in terms of results compared to the major international markets? Results point to an affirmative answer. The Hurst exponent shows that long-term dependence is probably linked not only to size or liquidity.